Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol. (15th January 2023) - Fu, Ce; Wang, Pan; Zhang, Rong-Hua; Yan, Luo-Yi; Cheng, Zheng; Zhang, Xin; Zhou, Xin-Wen
Highlights: The 3D PdIr uniform alloy with KI showed enhanced MOR activity and stability, confirmed with the theoretical calculation. The KI can be used to regulate the structure and surface composition of PdIr catalysts. The 3D structure, bifunctional mechanism, synergistic catalytic and electronic structure of Ir are the main reasons for the enhanced MOR performance. Abstract: Pure iridium (Ir) is easy to produce OH adsorbent species and has a wide range of applications in electrocatalysis. The structure–activity relationship between controlled synthesis and surface regulation of Ir-based alloys and their properties needs further study. When P123(poly (ethylene oxide)-poly (ethylene oxide)-poly (ethylene oxide)(PEO20 -PPO70 -PEO20 ) is used as reducing agent and protective agent, the ir-rich core–shell structure PdIr@Ir catalyst can be obtained by the solution thermal method without adding KI, and the PdIr alloy can be obtained after the addition of KI. The complexation ability of KI can change the reduction rate of the precursor and regulate the surface composition of the catalyst. After optimizing the dose of KI, the PdIr-4 shows the highest methanol oxidation reaction (MOR) activity and anti-CO toxicity. The PdIr-2 catalysts with rich Ir on the surface showed high stability, possibly due to the gradual activation of Ir on the surface by PdIr inside. The results of experimental characterization and theoretical calculations show that the main reasons for the performance improvement of PdIr series catalysts are the special three-dimensional structure of PdIr, the bifunctional mechanism between Pd and Ir, especially the synergistic catalytic action of Ir and the effect of regulating the electron structure. The experimental results of this paper are expected to provide some ideas and guidance for Ir-based catalysts with high activity and high stability.